Efficacy of daily versus alternate day oral iron supplementation for management of anaemia among general population: a systematic review and meta-analysis - Anupkumar D. Dhanvijay; Vipin Patidar; Jayvardhan Singh; Subodh Kumar; Shiv Kumar Mudgal; Seshadri Reddy Varikasuvu; Rajesh Kumar (BMC Pharmacology and Toxicology)
Abstract Background Iron deficiency anemia (IDA) remains a prevalent global health issue. While oral iron therapy is the first-line treatment, the optimal dosing strategy—daily versus alternate-day—remains debated, especially for general population use. Therefore, this review aimed to compare the efficacy and tolerability of daily versus alternate-day oral iron supplementation for IDA in the general population. Methods Searches were conducted across major databases through March 2025. Risk of bias was evaluated utilizing the Cochrane RoB 2 tool, and the certainty of evidence was graded using GRADE. The primary outcome was change in hemoglobin concentration; secondary outcomes included serum iron, ferritin, transferrin saturation, TIBC, MCV, and adverse events. R Studio software, version 4.2.3, and RevMan used for all analyses. Results This SRMA (systematic review and meta-analysis) included 11 RCTs involving 1014 participants. The pooled analysis found a small, statistically non-significant increase in hemoglobin with daily dosing over alternate-day (MD: 0.28, 95% CI: −0.01 to 0.56, p = 0.06, z = 1.91). Secondary outcomes revealed no significant differences among groups for serum iron, ferritin, transferrin saturation, TIBC, and MCV. Adverse effects were similar between groups (RR: 1.07, 95% CI: 0.86 to 1.34), though metallic taste was more frequent with daily dosing. Risk of bias was low to moderate across studies. Certainty of evidence was rated very low for most outcomes due to heterogeneity and imprecision. Conclusion Both daily and alternate-day oral iron supplementation are comparably effective for treating IDA, with alternate-day dosing showing better tolerability. Due to low certainty in evidence, treatment decisions should be individualized pending further high-quality research. Clinical trial number Not applicable.